Use of B-mode ultrasonography for sex determination and maturation monitoring in Prochilodus brevis (Steindachner 1875) - Sandra Brito Salmito-Vanderley, Carminda; Emidio Leite Moraes Ferreira, Pedro; Barbosa de Souza, Mirley; Melo Madeira, Guilherme; Farias Brito, Bruna; Correia Magalhães, Lívia; Henrique Sousa de Melo, Carlos; Rubens Montenegro, Assis (Revista Ciência Agronômica, 2023)
The Brazilian bocachico is a rheophilic fish from the northeast region of Brazil that holds great economic and scientific interest. The absence of evident sexual dimorphism and the invasive character of sexing methods and evaluation of gonadal maturation are obstacles to its artificial reproduction. In this scenario, ultrasonography emerges as a non-invasive method for sexing. The objectives of this study were to establish an ultrasound sexing method for Brazilian bocachico and select equations to estimate the gonadosomatic index (GSI), gonad weight (GW), and gonad volume (GV) of live bocachico. A total of 32 bocachico fish (18 females and 14 males) were analyzed ultrasonographically and morphologically. The association of morphometric and ultrasonographic parameters was investigated using Pearson Correlations. The following prediction equations were selected using multiple regression analysis: GSI = 16.22 × transvarea; GW = 30.3 × transvarea; and GV = 0.001260036 × pixels. A model capable of predicting the sex of the animals based on the ultrasonographic parameters was obtained using partial least-squares discriminant analysis with principal component analysis. The significance level adopted was P < 0.05. In conclusion, ultrasonography is a useful tool to perform sexing and evaluate the gonads during the breeding season, contributing to artificial reproduction in captivity.